The Number Poems: Forms of Construction, Constructions of Form - Welton, Matthew (2021)
This is the thesis component of a PhD by publication. The publication is The Number Poems by Matthew Welton (Carcanet, 2016). The thesis is an explication of the book, focusing on the poetics of its use of literary form.